Sm29, but not Sm22.6 retains its ability to induce a protective immune response in mice previously exposed to a Schistosoma mansoni infection. - Clarice Carvalho Alves; Neusa Araujo; Viviane Cristina Fernandes dos Santos; Flávia Bubula Couto; Natan R G Assis; Suellen B Morais; Sérgio Costa Oliveira; Cristina Toscano Fonseca (Public Library of Science (PLoS), 2015)
BACKGROUND:A vaccine against schistosomiasis would have a great impact in disease elimination. Sm29 and Sm22.6 are two parasite tegument proteins which represent promising antigens to compose a vaccine. These antigens have been associated with resistance to infection and reinfection in individuals living in endemic area for the disease and induced partial protection when evaluated in immunization trials using naïve mice. METHODOLOGY/PRINCIPALS FINDINGS:In this study we evaluated rSm29 and rSm22.6 ability to induce protection in Balb/c mice that had been previously infected with S. mansoni and further treated with Praziquantel. Our results demonstrate that three doses of the vaccine containing rSm29 were necessary to elicit significant protection (26%-48%). Immunization of mice with rSm29 induced a significant production of IL-2, IFN-γ, IL-17, IL-4; significant production of specific antibodies; increased percentage of CD4+ central memory cells in comparison with infected and treated saline group and increased percentage of CD4+ effector memory cells in comparison with naïve Balb/c mice immunized with rSm29. On the other hand, although immunization with Sm22.6 induced a robust immune response, it failed to induce protection. CONCLUSION/SIGNIFICANCE:Our results demonstrate that rSm29 retains its ability to induce protection in previously infected animals, reinforcing its potential as a vaccine candidate.